2023
DOI: 10.1021/acs.jafc.2c08522
|View full text |Cite
|
Sign up to set email alerts
|

Host Defense Peptides in Nutrition and Diseases: A Contributor of Immunology Modulation

Abstract: Host defense peptides (HDPs) are primary components of the innate immune system with diverse biological functions, such as antibacterial ability and immunomodulatory function. HDPs are produced and released by immune and epithelial cells against microbial invasion, which are widely distributed in humans, animals, plants, and microbes. Notably, there are great differences in endogenous HDP distribution and expression in humans and animals. Moreover, HDP expression could be regulated by exogenous substances, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 159 publications
0
7
0
Order By: Relevance
“…Furthermore, carbohydrate metabolism, including pyruvate, glycolysis and butanoate metabolisms, reflects not only WSC consumption but also taste and palatability (Du et al, 2021b). Amino acid metabolism reflects the capacity to degrade the high-molecularweight protein into amino acids and peptides, including ammonia formation and functional substrate production, such as antimicrobial and bioactive peptides Lai et al, 2022;Wang et al, 2022;Dou et al, 2023). Therefore, the high incidence of the global metabolism pathways in the bran treatment groups is conducive to improving the quality of the final fermentative products.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, carbohydrate metabolism, including pyruvate, glycolysis and butanoate metabolisms, reflects not only WSC consumption but also taste and palatability (Du et al, 2021b). Amino acid metabolism reflects the capacity to degrade the high-molecularweight protein into amino acids and peptides, including ammonia formation and functional substrate production, such as antimicrobial and bioactive peptides Lai et al, 2022;Wang et al, 2022;Dou et al, 2023). Therefore, the high incidence of the global metabolism pathways in the bran treatment groups is conducive to improving the quality of the final fermentative products.…”
Section: Discussionmentioning
confidence: 99%
“…As an innate immune factor of multicellular organisms, antimicrobial peptides (AMPs) are small-molecule proteins with potent antibacterial, antiviral, and antifungal activities, thus having favorable development prospects in food safety concerns. [14][15][16][17] Nowadays, with the deep study of AMPs, rational modification of natural AMPs and de novo designed AMPs have become an important approach for improving the antimicrobial properties of AMPs, 18 including site-directed amino acid substitutions, 19 amino acid end-tagging, 20 and design of linear pseudo-peptides. 21 However, although numerous studies about AMPs as food preservatives have been reported, they still have some drawbacks, including high synthetic cost, poor antimicrobial activity, and a narrow antimicrobial spectrum, which limit their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, conventional physical and chemical sterilization methods are not suitable because these will either compromise the quality of the fruit juice or lead to antibiotic resistance. In contrast, antimicrobial peptides have been demonstrated to not only exhibit broad-spectrum antibacterial activity but also have low cytotoxicity and contribute toward a restrained development of bacterial resistance. Moreover, natural products, bacteriocin, antibacterial peptides, and so on, have also been investigated for inhibiting A. acidocaldarius .…”
Section: Introductionmentioning
confidence: 99%